Kenya: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty - Breisinger, Clemens; Diao, Xinshen; Dorosh, Paul; Mbuthia, Juneweenex; Omune, Lensa; Oseko, Edwin Ombui; Pradesha, Angga; Thurlow, James (2022)
Presentation prepared by Clemens Breisinger, Xinshen Diao, Paul Dorosh, Juneweenex Mbuthia, Lensa Omune, Edwin Ombui Oseko, Angga Pradesha, and James Thurlow, all with the International Food Policy Research Institute, Washington, DC. This is part of the Global Crisis Country Series.